2017
DOI: 10.1080/09593330.2017.1344324
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration fouling propensity caused by wastewater effluent organic matters and surface-water dissolved organic matters

Abstract: Rejection of dissolved organic matters (DOMs) from wastewater treatment plant effluent (EfOM) and surface reservoir water (RW-DOM) by nanofiltration (NF) was comparatively studied to evaluate their influence on membrane fouling and to unveil the major causations. EfOM and RW-DOM were fractionated to determine the major components that preferentially form fouling layer and initiate biofouling. The results indicated that EfOM induced a rapid membrane permeability loss and a more complicated biofilm diversity tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…The top three most frequent classes of organisms were in Proteobacteria , including, Alphaproteobacteria , followed by Gammaproteobacteria and Betaproteobacteria . These results were supported by results found in [ 21 , 44 , 77 , 79 , 80 ]. For example, in Hörsch et al [ 81 ], researchers found Alphaproteobacteria to be the most abundant class of organisms on RO membranes, followed by Gammaproteobacteria .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The top three most frequent classes of organisms were in Proteobacteria , including, Alphaproteobacteria , followed by Gammaproteobacteria and Betaproteobacteria . These results were supported by results found in [ 21 , 44 , 77 , 79 , 80 ]. For example, in Hörsch et al [ 81 ], researchers found Alphaproteobacteria to be the most abundant class of organisms on RO membranes, followed by Gammaproteobacteria .…”
Section: Discussionsupporting
confidence: 89%
“…This semi-systematic review for question 2 determined thirty-three phyla of organisms corresponding to forty-four classes of organisms that were identified in various studies via 16S rRNA analysis in biofouling samples from RO systems. Similar to results from question 1, the most common organisms identified were in the phylum Proteobacteria [ 21 , 44 , 79 ]. The top three most frequent classes of organisms were in Proteobacteria , including, Alphaproteobacteria , followed by Gammaproteobacteria and Betaproteobacteria .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Otherwise, it is non-reversible. In [20,21] it was documented that in the case of the nanofiltration of effluents from urban wastewater treatment plant fouling is usually reversible.…”
Section: Capacity Of the Membranesmentioning
confidence: 99%